The Evolution of the GPCR Signaling System in Eukaryotes: Modularity, Conservation, and the Transition to Metazoan Multicellularity - de Mendoza, Alex (Oxford University Press, 2014)
The G-protein-coupled receptor (GPCR) signaling system is one of the main signaling pathways in eukaryotes. Here, we analyze the evolutionary history of all its components, from receptors to regulators, to gain a broad picture of its system-level evolution. Using eukaryotic genomes covering most lineages sampled to date, we find that the various components of the GPCR signaling pathway evolved independently, highlighting the modular nature of this system. Our data show that some GPCR families, G proteins, and regulators of G proteins diversified through lineage-specific diversifications and recurrent domain shuffling. Moreover, most of the gene families involved in the GPCR signaling system were already present in the last common ancestor of eukaryotes. Furthermore, we show that the unicellular ancestor of Metazoa already had most of the cytoplasmic components of the GPCR signaling system, including, remarkably, all the G protein alpha subunits, which are typical of metazoans. Thus, we show how the transition to multicellularity involved conservation of the signaling transduction machinery, as well as a burst of receptor diversification to cope with the new multicellular necessities.